Synergistic effects in hydrodynamic cavitation abrasive finishing for internal surface-finish enhancement of additive-manufactured components - Nagalingam, Arun Prasanth (2020)
Surface finishing additive-manufactured (AM) internal channels is challenging. In this study, a novel hydrodynamic cavitation abrasive finishing (HCAF) technique is proposed and its feasibility for surface finishing is analyzed. Surface finishing is performed using controlled hydrodynamic cavitation erosion and microparticle abrasion phenomena. Various surface-finishing conditions were employed to investigate material removal and surface finish enhancement via synergistic effects in the HCAF process. To quantify the contributions from each erosion mechanism, additively manufactured AlSi10Mg internal channels were surface finished in isolated conditions of a) liquid impingement, b) absolute cavitation erosion, c) absolute abrasion, and d) cavitation-assisted microparticle abrasion. The erosion rate and total thickness loss were established as the measurands to quantify the intensity of the surface finish. The synergistic effects yielded 80% higher material removal and over 90% (Ra) higher surface-finish enhancement in HCAF conditions than those from pure cavitation and abrasion. A synergy map is proposed to quantify the contribution from the synergistic effects from hydrodynamic cavitation abrasive finishing. The synergistic material-removal mechanism is explained using surface morphology observations. Hydrodynamic cavitation gradually removed loosely attached surface asperities in AM internal channels. The microabrasives present in the cavitating flow enhanced the erosion favorably, creating a synergistic effect that resulted in significantly improved material removal and surface finish quality. The findings suggest that the synergistic effects in hydrodynamic cavitation abrasive finishing are effective in enhancing the material removal and surface finish quality of AM components.